Folic Acid Attenuates N-Methyl-N’-Nitro-N-NitrosoguanidineInduced Gastric Mucosal Injury in Rats - Peng, Caiting; Wang, Li; Liang, Yuan; Che, Li; Sun, Rongjing; Yu, Jia; Gong, Jiamin; Wang, Dandan; Cheng, Suizhi; Yang, Qingqing; Jing, Tao; Liu, Zhenzhong (Turkish Journal of Gastroenterology, 2024)
Background/Aims: N-Methyl-N’-nitroso-N-nitrosoguanidine (MNNG) is suspected to increase the risk of developing stomach cancer. Folic acid (FA) is familiar with decreasing inflammation. We expected that FA would protect against MNNG-induced gastric mucosal injury. Materials and Methods: Thirty 12-week-old SPF-grade female Sprague-Dawley (SD) rats were treated with MNNG and given different dosages of FA as an intervention measure. Quantitative polymerase chain reaction (qPCR) was used to analyze the expression of IL-1, IL-6, IL-8, IL-18, TNF-α, NLRP3, ASC, and caspase-1 genes. The enzyme-linked immunosorbent assay (ELISA) was utilized for the identification of inflammatory cytokines. Western blot was accustomed to detecting IL-1β, IL-18, and NLRP3 inflammatory vesicles in gastric tissue. Furthermore, the gastric mucosal tissues underwent histological examination. Results: Our investigation demonstrated that FA reduced MNNG-induced inflammatory factor increase by decreasing NF-κB signaling (P < .05). Furthermore, FA prevented the MNNG-induced upregulation of NLRP3 inflammasome-related genes and proteins (all P < .01). Conclusion: Our data imply that MNNG exposure stimulates the NF-κB/NLRP3 pathway, while FA suppresses it, limiting stomach mucosal inflammation. Cite this article as: Peng C, Wang L, Liang Y, et al. Folic acid attenuates N-methyl-N’-nitro-N-nitrosoguanidine-induced gastric mucosal injury in rats. Turk J Gastroenterol. 2024;35(11):839-848.